Assessing the failure in transfer of passive immunity in beef calves: two case reports - Carolina Balao Silva; Lina Costa; Rute Santos; Luisa Pereira; Henrique Pinto; Helga Waap (Instituto Politécnico de Viseu, 2020)
Introduction: Failure in Transfer of Passive Immunity (FTPI) is a condition that occurs frequently in the bovine species when inadequate ingestion or absorption of enough good-quality colostrum takes place. In bovine kept in extensive conditions, FTPI diagnosis is usually made by complete physical examination, with not enough time for laboratory analysis, and treatment is based on the administration of colostrum replacement products or transfusion. Objectives: To evaluate the transfer of passive immunity in meat calves kept in extensive conditions. Methods: We hereby describe two case reports of calves presenting clinical signs compatible with FTPI and their biochemical analysis, including IgG determination by an ELISA test. Results: The results indicated that both calves presented a very low serum IgG concentration (calf 1: 0.7mg/ml and calf 2: 1mg/ml), confirming FTPI. The animals were treated with a plasma transfusion from a crossbreed cow. At 24 hours after the plasma transfusion, serum IgG concentration raised slightly on both animals, but after 48 hours serum IgG reduced to a concentration similar to the pre-transfusion values. Conclusions: We conclude that plasma transfusion can be an effective treatment for FTPI in clinical cases in extensive conditions but it has to be monitored assuring that serum IgG concentration reaches normal values. Immunological status of donors should be assessed before plasma collection and transfer.